Long‐distance seed dispersal by wind: disentangling the effects of species traits, vegetation types, vertical turbulence and wind speed. Issue 4 (17th May 2014) - Heydel, Felix; Cunze, Sarah; Bernhardt‐Römermann, Markus; Tackenberg, Oliver
Abstract: Long‐distance dispersal (LDD) of plant seeds by wind is affected by functional traits of the species, specifically seed terminal velocity and height of seed release above the vegetation cover (HAC), as well as by the meteorological parameters wind speed and vertical turbulence. The relative importance of these parameters is still under debate and the importance of their variability in vegetation types, sites and years has only rarely been quantified. To address these topics, we performed simulation studies for different vegetation types, sites, years and plant species with PAPPUS, a process based trajectory model. We found that LDD (measured in terms of migration rates) was higher in forests compared to open landscapes. Forests also showed greater between‐year variability in LDD. Terminal velocity had an effect on LDD in both vegetation types, while the effect of HAC was significant only in the open landscape. We found considerable differences in how vertical turbulence and wind speed affect LDD between species and vegetation types: In the open landscape the strength of the positive relationship between vertical turbulence and LDD generally decreases with terminal velocity, whereas it increases in forests. The strength of the predominantly positive effect of wind speed on LDD increases with terminal velocity in both vegetation types, while in forests we found even negative relationships for species with low terminal velocity. Our results generally suggest that the effects of vertical turbulence and wind speed on LDD by wind diverge for species with different functional traits as well as in different vegetation types.